Persuasive bodies: Testimonies of deep brain stimulation and Parkinson's on YouTube. (February 2019) - Gardner, John; Warren, Narelle; Addison, Courtney; Samuel, Gabby
Abstract: Contemporary publics actively engage with diverse forms of media when seeking health-related information. The hugely popular digital media platform YouTube has become one means by which people share their experiences of healthcare. In this paper, we examine amateur YouTube videos featuring people receiving Deep Brain Stimulation (DBS) for the treatment of Parkinson's disease. DBS has become a widely implemented treatment, and it is surrounded by high expectations that can create difficulty for clinicians, patients and their families. We examine how DBS, Parkinson's disease, and DBS recipients themselves, are delineated within these YouTube videos. The videos, we demonstrate, contain common compositional and stylistic elements that collectively represent DBS as a technological fix, and which accentuate the autonomy of the DBS recipient. The relational, interpersonal dimensions of chronic illness, and the complex impact of DBS on family dynamics, are elided. We therefore shed light on the means by which high expectations regarding DBS are sustained and circulated, and more generally, we illustrate how potentially powerful representations of medical technologies can emerge from the intersection of social media platforms, afflicted bodies and patient narratives. Highlights: YouTube has become a forum for sharing experiences of deep brain stimulation (DBS). Amateur YouTube videos configure DBS as a technological fix. Videos often elide the complexity of chronic illness and its treatment. Videos thus sustain expectations that technologies enhance patient independence. Powerful portrayals emerge from intersections of social media, bodies & narratives.